IMPLEMENTASI PENERAPAN SANKSI TINDAK PIDANA PEMILU Di PROVINSI SULAWESI SELATAN - Zulfakar, Andi Baso (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2024)
In the application of sanctions for election crimes in the province of South Sulawesi Government Regulation in Lieu of Law Number 1 of 2022 and Article 1 number 1 concerning election offenses against election administration violations. This type of research is descriptive qualitative research. This research was conducted to collect a number of information in the field from a questionnaire of employees and Acting KPU during the general election organizers in this case the chairman in terms of fraud and political money during the election celebration of South Sulawesi province Makassar city. The research location was conducted in Makassar City. This location was chosen because it has all the supporting aspects in order to run well and Makassar City is famous as a political central area in South Sulawesi.